CODE SWITCHING AND LANGUAGE TRANSFERS (American Journal of Research in Humanities and Social Sciences, 2025)
This article analyzes the distinctions and overlaps between code-switching and language transfer in multilingual communication. It clarifies their linguistic mechanisms, speaker proficiency requirements, and functions, while also explaining related concepts such as code-meshing, translanguaging, and translingualism. The paper provides clear definitions and resolves common terminological confusion in linguistic research.